Integrasi Office Add-On (Onlyoffice) Untuk Meningkatkan Fungsi Nextcloud Di Politeknik Negeri Tanah Laut - Khairul Anwar hafizd; M. Najamudin Ridha; Eka Wahyu Sholeha; Fathurrahmani; Herpendi (Cattleya Darmaya Fortuna, 2023)
In the contemporary digital age, effective management and collaborative use of files are essential for the efficient operation of administrative and educational activities. As a result, there is a significant demand for a more secure, self-sufficient, and well-managed solution. An initial survey was conducted among the faculty, staff, and students of Politeknik Negeri Tanah Laut to investigate their utilization of Google Drive services. The primary goal of this survey is to gain a deeper insight into the requirements and preferences of users with respect to file storage and collaboration. The implementation process of Nextcloud, including its installation, configuration, and reliability and security testing as an object storage provider, is underway within the Politeknik Negeri Tanah Laut environment. To evaluate the effectiveness of Nextcloud as a replacement for Google Drive at Politeknik Negeri Tanah Laut, we will analyze the survey results and the progress of Nextcloud implementation. Special attention will be given to aspects such as security, scalability, and data availability. We will also assess whether Nextcloud can meet the collaborative and file-sharing needs of Politeknik Negeri Tanah Laut. The outcomes of this research are expected to provide a clearer understanding of Nextcloud's capabilities as a superior and more secure choice for object storage in an educational setting. Additionally, these findings may be valuable for other educational institutions seeking alternative solutions for managing their data and files.